Use of waste oil for the manufacture of explosives in the mining industry (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the potential use of waste engine oil in the production of explosives, contributing to waste recycling and cost reduction in the mining industry. The environmental and economic advantages of this approach are presented, and the key technological processes for integrating waste oil into explosive production are discussed. Examples of successful implementation of such projects at mines in Russia are highlighted. Thus, the use of waste engine oil in the production of explosives not only effectively addresses the issue of industrial waste disposal but also contributes to enhancing environmental safety and reducing operational costs in the mining industry.
Keywords: ecology, toxic substances, waste oil, explosives recycling